2023
DOI: 10.3389/fneur.2022.1041263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factor and outcome in middle-aged and elderly population affected by hemiplegic shoulder pain: An observational study

Abstract: BackgroundHemiplegic shoulder pain is the most common complication after stroke. It usually occurs during the critical period of stroke recovery and hinders the rehabilitation of upper extremity motor function. However, there are few studies on the risk factors, the development and prognosis of shoulder pain after stroke.ObjectivesThis study aimed to observe the prevalence of post-stroke shoulder pain in the middle-aged and elderly population, find out the risk factors for post-stroke shoulder pain, and explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
1
5
0
1
Order By: Relevance
“…и у 75% -в течение первого года после инсульта [41][42][43]. По данным недавно опубликованного исследования, проведенного Y. Li et al [44], среди 239 пациентов с инсультом, которые были госпитализированы в реабилитационное отделение и обследовались в течение одного года, распространенность гемиплегической боли в плече составила 55,6% (133/239) при поступлении, 59,4% (142/239) через 2 мес. и 55,1% (130/236) через 4 мес.…”
Section: постинсультная боль в плечеunclassified
“…и у 75% -в течение первого года после инсульта [41][42][43]. По данным недавно опубликованного исследования, проведенного Y. Li et al [44], среди 239 пациентов с инсультом, которые были госпитализированы в реабилитационное отделение и обследовались в течение одного года, распространенность гемиплегической боли в плече составила 55,6% (133/239) при поступлении, 59,4% (142/239) через 2 мес. и 55,1% (130/236) через 4 мес.…”
Section: постинсультная боль в плечеunclassified
“…Hemiplegic shoulder pain (HSP), also known as poststroke shoulder pain, is one of the most common complications after stroke and often affects patients’ quality of life (Li et al., 2022 ). HSP usually occurs 2 or 3 months after stroke (Anwer & Alghadir, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence rate of HSP varies from 10% to 20%, and its prevalence rate varies from 8% to 47% (Anwer & Alghadir, 2020 ; Menoux et al., 2019 ; Nadler et al., 2020 ; Zhang et al., 2021 ). The pathogenesis of HSP includes impaired motor control, altered activity of the peripheral or central nervous system, and soft tissue injury, which may occur independently or in concert (Li et al., 2022 ; Wilson & Chae, 2015 ). In clinical practice, HSP can be diagnosed by history, musculoskeletal examination, neurological examination, and imaging and can be treated by proper arm handling and positioning, exercise therapy, physical factor therapy, and medication (Dyer et al., 2020 ; Wilson & Chae, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 A recent study reported that 46 of 239 patients with stroke (19%) had shoulder subluxation. 2 Moreover, sustained elongation of the shoulder muscles and capsule or shoulder joint motion causes shoulder pain. 3 Patients with shoulder pain show worse functional prognoses and longer hospital stays than those without pain.…”
mentioning
confidence: 99%